1990
DOI: 10.1021/j100387a004
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the soluble all-carbon molecules C60 and C70

Abstract: component (t = 4.7 ns). This rvalue is consistent with previous (room temperature) estimates of donor-acceptor center to center distance of 25 A. The most important result is that the simplified kinetics at room temperature argue that any structural states of the complex which arc trapped at 77 K are largely equilibrated at 300 K within 5 ns. This result suggests that motion at the cytc/ccp interface can be quite rapid and offers experimental support for the rapid restricted dimensional diffusion model of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
159
0
8

Year Published

1991
1991
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 818 publications
(177 citation statements)
references
References 0 publications
10
159
0
8
Order By: Relevance
“…Твердые фуллерены, иногда называемые фуллеритами, представляют собой по-лупроводники, которые характеризуются шириной запрещенной зоны 1,5-1,95 эВ (С 60 ) [58,141 ], 1,91 эВ (С 70 ) [142] и 1,2эВ (C 84 ) [143]. Детальные исследо-вания зависимостей электрических характеристик поликристаллических образцов С 60 от давления и температуры выполнены авторами работ [143][144][145].…”
Section: э лunclassified
“…Твердые фуллерены, иногда называемые фуллеритами, представляют собой по-лупроводники, которые характеризуются шириной запрещенной зоны 1,5-1,95 эВ (С 60 ) [58,141 ], 1,91 эВ (С 70 ) [142] и 1,2эВ (C 84 ) [143]. Детальные исследо-вания зависимостей электрических характеристик поликристаллических образцов С 60 от давления и температуры выполнены авторами работ [143][144][145].…”
Section: э лunclassified
“…Cc0 and C,, were produced by arc heating graphite in helium (100-150 Torr pressure) [4,5,7], and removing the fullerenes from the raw soot by toluene extraction. Purification and separation of CbO and CT0 was accomplished by chromatography using a column of activated alumina eluted with hexane and hexane/benzene mixtures [23,24]. Mass spectrometry indicated that the separated ChO contained 6 1% CD, while the C,n fractions had < 5% CeO.…”
mentioning
confidence: 99%
“…One of the most exciting properties of fullerene chemistry is related to their excited-state properties [10,11]. The most abundant representative of the family C 60 can be identified via its strong absorptions between 190 and 410 nm (allowed 1 T 1u -1 A g ) as well as by some pale but significant transitions in the 410 and 620 nm (orbital forbidden singlet-singlet) region which is responsible for the purple color of C 60 and the red color of C 70 [12,13].…”
Section: Optical Studies Of Fullerenementioning
confidence: 99%